PENGARUH KINERJA LINGKUNGAN TERHADAP PRAKTIK PENGUNGKAPAN SUSTAINABILITY REPORT dan KINERJA EKONOMI - Felecia Novita Iriyanto; Paskah Ika Nugroho (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2014)
This study examines the effect of environmental performance measured from PROPER ( Performance Rating Program in Environmental Management ) towards sustainability report disclosure practices and economic performance . Sustainability Report ( SR ) was measured by 79 items of disclosure by the GRI G3 (2006) , while the economic performance using scale industries calculated return of Al - Tuwaijiri , et al . (2004) . Samples in this study were taken by purposive sampling technique that companies listed on the Stock Exchange and publish an annual report in 2011-2012 . The statistical methods used in this study is a simple regression analysis to examine the effect of environmental performance on sustainability report and multiple regression analysis to examine the effect of environmental performance and sustainability report on economic performance . Data analysis and hypotheses tests in this study using SPSS version 16. Results showed that the company's environmental performance have a significant positive effect on Sustainability Report Diclosure. Meanwhile, the results of the second hypothesis shows that environmental performance has a significant impact on economic performance. And the results showed that the third hypothesis Sustainability Report Diclosure have a significant positive effect on economic performance .Keywords : Global Reporting Initiative , Sustainability Reporting , Economic Performance , Environmental Performance